Project DEMETER: Concept Note for an Emerging Risks Knowledge Exchange Platform (ERKEP) Framework. Issue 12 (13th December 2018) - Meijer, Nathan; Filter, Matthias; Clark, Beth; Józwiak, Ákos; Comber, Rob; Mylord, Teresa; Kerekes, Kata; Willems, Don; van Asselt, Esther; Frewer, Lynn; Czyz, Michal‐Jan; Fischer, Arnout; et al.
Abstract : Researchers, governments, agencies, food producers and the civil society are increasingly concerned about 'emerging food risks'. It is recognised that the successful identification of emerging risks is at the heart of protecting public health and the environment, and that this requires worldwide cooperation between all parties involved in the food supply chain. The objectives and research proposed in the DEMETER project are designed to support current (and future) EFSA procedures for emerging issue and risks identification, providing a community resource that will allow EFSA and EU Member State authorities to share data, data mining knowledge and methods in a rapid and effective manner. A prototype technical Platform called the Emerging Risks Knowledge Exchange Platform (ERKEP) will be developed by DEMETER. The 'Concept Note' is a vison document on a framework of Emerging Risk Knowledge Exchange in which ERKEP is embedded in – but goes beyond the ERKE platform. Outlined in this document are: definitions of relevant concepts in the context of emerging issues and risks identification; who are the contributors, users and stakeholders of ERKEP; what are the identified end‐user needs, how could the ERKEP Framework contribute to meeting these needs; what types of knowledge, data, and methods do they share; and how can a technical solution be implemented to support these activities.